Corneal wound healing - Wilson, Steven E. (Experimental eye research, 2020)
The corneal wound healing response is typically initiated by injuries to the epithelium and/or endothelium that may also involve the stroma. However, it can also be triggered by immune or infectious processes that enter the stroma via the limbal blood vessels. For mild injuries or infections, such as epithelial abrasions or mild controlled microbial infections, limited keratocyte apoptosis occurs and the epithelium or endothelium regenerates, the epithelial basement membrane (EBM) and/or Descemet's basement membrane (DBM) is repaired, and keratocyte- or fibrocyte-derived myofibroblast precursors either undergo apoptosis or revert to the parent cell types. For more severe injuries with extensive damage to EBM and/or DBM, delayed regeneration of the basement membranes leads to ongoing penetration of the pro-fibrotic cytokines transforming growth factor (TGF) β1, TGFβ2 and platelet-derived growth factor (PDGF) that drive the development of mature alpha-smooth muscle actin (SMA)+ myofibroblasts that secrete large amounts of disordered extracellular matrix (ECM) components to produce scarring stromal fibrosis. Fibrosis is dynamic with ongoing mitosis and development of SMA + myofibroblasts and continued autocrine-or paracrine interleukin (IL)-1-mediated apoptosis of myofibroblasts and their precursors. Eventual repair of the EBM and/or DBM can lead to at least partial resolution of scarring fibrosis. •Keratocyte apoptosis is the first observable stromal event after anterior corneal injury.•Normal or defective regeneration of the EBM controls regenerative vs. fibrotic healing.•Descemet's membrane modulates regenerative vs. fibrotic healing for posterior injuries.•Fibrosis is dynamic with ongoing mitosis, development and apoptosis of myofibroblasts.